PRODUKTIVITAS TANAMAN Asystasia gangetica (L.) Subsp. Micrantha YANG DIPUPUK LIMBAH BUAH NAGA - N. M., WITARIADI; KUSUMAWATI, N. N. C. (Majalah Ilmiah Peternakan, 2023)
The experiment aimed to determine the productivity of A. gangetica (L.) Subsp. Micrantha fertilized by dragon fruit waste. The experiment lasted for 3 months, with a completely randomized design (CRD) consisting of 5 treat- ments and 8 replications. The treatments were: D0: 0 l ha-1, D1: 2.500 l ha-1, D2: 5.000 l ha-1, D3: 7.500 l ha-1 and D4: 10.000 l ha-1. Variables observed: plant height, number of tillers, number of branches, number of leaves, leaf area per pot, dry weight of leaves, dry weight of stems, ratio of leaf dry weight to stem dry weight, total dry weight of forage, root dry weight, and weight ratio total dry weight of forage by root dry weight. The results showed that the utilization of dragon fruit waste as liquid organic fertilizer could increase the productivity of A. gangetica (L.) subsp. Micrantha. Treatment with fertilizer dosage of 2.500-10.000 l ha-1 was able to increase plant productivity in all variables except for the ratio of leaf dry weight to stem dry weight and the ratio of total dry weight of forage to root dry weight gave the same results. The dosage 10.000 l ha-1 is the best dosage in producing the highest produc- tivity compared to other treatments. It can be concluded that the utilization of dragon fruit waste as liquid organic fertilizer can increase the productivity of A. gangetica (L.) subsp. Micrantha the best dosage with at 10,000 l ha-1